Passengers’ perception of public transport information systems - Bachok, Syahriah; Mohd Maksid, Noor Hafiza; Yaacob, Noor Alyani; Paiman, Tuminah; Abdul Razak, Sarah; Mohamed Osman, Mariana (2011)
This paper compares the perception towards public transportation information system in selected cities. Two viewpoints, each from the first time users and frequent travelers were recorded in a likert-scale checklist. Audio and visual capturing of data about the system was conducted through voice recording and photo taking. A regression analysis has been conducted on a dependent variable which is the average scoring for accessibility and reliability of information system. Independent factors found to be significantly affecting user perception were whether users were frequent travelers, the proportion of distance travelled by public transport and the duration of non-stop travel by public transport.